"Rule of Spence" and Dickman's Classification of Transverse Atlantal Ligament Injury Revisited: Discrepancy of Prediction on Atlantoaxial Stability Based on Clinical Outcome of Nonoperative Treatment for Atlas Fractures. Issue 5 (1st March 2019) - Liu, Peng; Zhu, Jun; Wang, Zhong; Jin, Yufei; Wang, Yingbo; Fan, Weili; Liu, Mingyong; Zhao, Jianhua
Abstract : Detailed clinical information of 13 adult patients with acute atlantal fractures underwent nonoperative treatment was retrospectively studied. "Rule of Spence" was found inaccurate in predicting either integrity of transverse atlantal ligament (TAL) or atlantoaxial stability, whereas Dickman's classification of TAL injury was more superior to "rule of Spence" on both prediction. Study Design: A retrospective study. Objective: To evaluate the prediction accuracy of "Rule of Spence" and Dickman's classification of the transverse atlantal ligament (TAL) injury on clinical outcomes (mainly focused on atlantoaxial stability) of atlas fractures treated nonoperatively. Summary of Background Data: TAL is regarded as primary stabilizer of the atlantoaxial complex. Atlas fractures are categorized as unstable and stable according to TAL injury or not. "Rule of Spence" and Dickman's classification have been widely used to evaluate the integrity of TAL indirectly or directly. However, there is controversy about how to interpret and apply these image measures appropriately in treatment decision making, and comparing the two measures in same cohort has been lack. Methods: From January 2013 to December 2015, 13 adult patients with atlas fractures, treated nonoperatively at acute posttraumatic phase and followed up for at least 2 years, were enrolled in the study. Lateral mass offset (LMO) and TAL injury were measured by radiography. Atlantoaxial stability, pain in occipital region, limitation of cervical motion, neurological dysfunction, and quality of daily life were evaluated as clinical outcomes. Results: LMO less than 6.9 mm was inaccurate either to exclud TAL injury (4/8, 50% failed) or to predict clinical outcomes (2/8, 25% failed), whereas LMO greater than 6.9 mm was accurate to determine TAL injury (5/5, 100% succeeded) but not to predict atlantoaxial stability (4/5, 80% failed). Two cases with Dickman's classification type I injury (100%) failed to restore C1-2 stability and six of seven type II (85.7%) succeeded. Three patients were indicated for fusion surgery due to instability, and one due to traumatic arthritis. Overall clinical outcomes were satisfactory as pain and quality of life were considered. Conclusion: Dickman's classification of TAL injury is of higher superiority to "Rule of Spence" in term of the accuracy of predicting atlantoaxial stability of nonoperatively treated atlas fractures. Level of Evidence: 4 Abstract : Supplemental Digital Content is available in the text